1969
DOI: 10.1002/1097-0142(196905)23:5<1210::aid-cncr2820230530>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors of cancer of the colon and rectumII. Japanese epidemiological data

Abstract: This is an epidemiological study of 107 patients with large bowel cancer and 307 control patients interviewed in Japan. Colon cancer is significantly less common in Japan, but rectal cancer is as common in Japan as it is in the United States. Japanese patients with cancer of the colon have a higher socioeconomic status than rectal cancer patients. Associated with the higher status is a more Western style diet. It is suggested that perhaps dietary fat influences the make‐up of the bacterial flora and thus affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(47 citation statements)
references
References 6 publications
3
43
0
1
Order By: Relevance
“…63 A sharp contrast was drawn between colon cancer rates in Japanese consuming traditional diets, and Americans consuming a "Western diet." 64 However, as Japanese immigrated to Hawaii and began consuming a 'Western diet', colon cancer rates rose midway between Japanese and American populations within two generations. 64,65 Another population that received particular attention were the Seventh Day Adventists, who consume a vegetarian diet and have significantly lower incidence of CRC relative to age-matched and socioeconomically similar cohorts in the American population who consume a Western diet.…”
Section: Deoxycholic Acid and Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…63 A sharp contrast was drawn between colon cancer rates in Japanese consuming traditional diets, and Americans consuming a "Western diet." 64 However, as Japanese immigrated to Hawaii and began consuming a 'Western diet', colon cancer rates rose midway between Japanese and American populations within two generations. 64,65 Another population that received particular attention were the Seventh Day Adventists, who consume a vegetarian diet and have significantly lower incidence of CRC relative to age-matched and socioeconomically similar cohorts in the American population who consume a Western diet.…”
Section: Deoxycholic Acid and Colon Cancermentioning
confidence: 99%
“…64 However, as Japanese immigrated to Hawaii and began consuming a 'Western diet', colon cancer rates rose midway between Japanese and American populations within two generations. 64,65 Another population that received particular attention were the Seventh Day Adventists, who consume a vegetarian diet and have significantly lower incidence of CRC relative to age-matched and socioeconomically similar cohorts in the American population who consume a Western diet. 66 Wynder et al (1967) first proposed an association between dietary fat and CRC, 67 and further proposed that dietary fat influences the fecal microbiota in a way that promotes CRC.…”
Section: Deoxycholic Acid and Colon Cancermentioning
confidence: 99%
“…The picture is further complicated when food groups were analysed. Starch-rich foods such as rice in Japan (Wynder et al, 1969), rice, cereal dishes and potatoes in Southern Europe (Macquart-Moulin et al, 1986; were found to be directly associated with colorectal cancer risk.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…PREVIOus epidemiological studies of bowel cancer (colonic and rectal cancer) have revealed several possible risk factors including obesity (Wynder and Shigematsu, 1967), constipation (Pernu, 1960;Higginson, 1966;Wynder and Shigematsu, 1967;Haenzel et al, 1973), use of laxatives (Boyd and Doll, 1954;Higginson, 1966;Wynder and Shigematsu, 1967), beer drinking (Wynder and Shigematsu, 1967; Stocks, 1957;Bjelke, 1974b), meat consumption (Haenszel et al, 1973;Rjelke, 1974a; Phillips, 1975), low fibre consumption (Modan et al, 1975), and other dietary factors (Wynder et al, 1969;Bjelke 1971Bjelke , 1973Haenzel et al, 1973), as well as race (Wynder et al, 1969;Haenszel et at., 1973) and geography (Wynder et al, 1969;Bjelke, 1971Bjelke, , 1973Haenszel et al, 1973). This entire subject has been exhaustively reviewed elsewhere by Bjelke (1974c), with additional contributions by Gori (1975) and Enstrom (1975a).…”
Section: Received 1 September 1976 Accepted 25 October 1976mentioning
confidence: 99%